PENGARUH LUAS LAHAN, TEKNOLOGI TERHADAP PRODUKSI DAN PENDAPATAN PETANI KOPI ROBUSTA DI DESA MUNDUK TEMU - Putra, I Kadek Wahyu Andika; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 10 (2020): VOL 9 NO 10, OKTOBER 2020 (2152 - 2389), 2020)
Coffee plantations have an important role to play in supporting the economy in Bali. One of them is in Munduk Temu Village, type of coffee that is widely produced is robusta coffee. This study aims 1) analyze the effect of land area, technology on production, 2) analyze the effect of land area, technology, and production on income and 3) analyze the indirect effects of land area and technology on income through the production of robusta coffee farmers in the village Munduk Temu. Samples were 40 robusta coffee farmers. Analysis technique used path analysis. The results analysis show, land area has a positive and significant effect on the production of robusta coffee farmers, technology has a positive and significant effect on robusta coffee production, land area has a positive and significant effect on the income of robusta coffee farmers, technology has no effect on the income of robusta coffee farmers. production has a positive and significant effect on the income of robusta coffee farmers. Production mediates indirectly the effect of land area on the income of robusta coffee farmers, technology does not have an indirect effect on income through the production of robusta coffee.   Keywords: land area, technology, production, income.